(untitled) (Scientific journal of the Fergana State University, 2026)
This article discusses the methods and advantages of how to complete technological tasks in primary education. Currently, our president is paying great attention to the education system. This includes caring for our students, the opportunities and conditions prepared for them, and creating all the opportunities for our young people to receive education. In turn, schoolchildren will find great convenience in completing tasks in mathematics and technology using algorithmic sequences.